A pilot study of an Enhanced Mental Health Assessment during routine and discharge medicals in the British Armed Forces. Issue 1 (11th June 2013) - Aguirre, Marcela; Greenberg, N; Sharpley, J; Simpson, R; Wall, C
Abstract : Objectives: A pilot study to assess the practicality of introducing an enhanced mental health assessment (EMHA) into all routine and discharge medicals of the UK Armed Forces in order to facilitate treatment prior to and on return to civilian life. Methods: A pilot study was conducted using an EMHA questionnaire with questions about depression, anxiety, post-traumatic stress disorder, alcohol use, sleep and anger/irritability. At pilot sites, the EMHA was completed during all routine and discharge medicals between May 2011 and July 2011. At the end of the study period, qualitative data were collected from participating medical officers and practice managers regarding their opinions about the pilot study. Results: The quantitative data revealed an average pick-up rate for mental health (MH) problems. Out of the four military medical centres who participated and the 325 questionnaires collected, one referral to a Department of Community Mental Health was made. 26 (8%) patients were categorised as ' some concern and patient offered advice and/or reassurance '. The vast majority of patients were found to have no evidence of MH problems. However, using a validated alcohol screening tool, 64% of service personnel were found to have a score indicating 'higher risk drinking'. Analysis of the qualitative data suggests that the EMHA is an easy tool to implement with minimal additional time and resources needed. The interviewees pointed out a number of limitations and suggestions for possible further studies. Conclusions: The pilot study successfully demonstrated that the EMHA questionnaire is easy to administer, does not take up a large amount of additional resources or manpower and provides a useful check of MH status. The study picked up an average number of MH cases and the questions on alcohol consumption highlighted that military personnel may be at a 'higher risk of drinking'.